Предмет: Математика, автор: Vshuldiakova

помогите пожалуйста .. срочно

Приложения:

Ответы

Автор ответа: NataMon
1

Ответ:

1. 3

2. 27 1/8

3. х = -3/13

Пошаговое объяснение:

1. (3х+2)² - (3х+4)(3х-2) при х = -3/2

(3х+2)² - (3х+4)(3х-2) = 9х² + 12х + 4 - 9х² - 12х + 6х + 8 =

6х + 12 = 6*(-3/2) + 12 = -9 + 12 = 3

2. (х+у)(х²-ху+у²) при х = 3, у = 1/2

(х+у)(х²-ху+у²) = х³ + х²у - х²у - ху² + ху² + у³ = х³ + у³ =

3³ + (1/2)³ = 27+1/8 = 27 1/8

3. (5х+1)(2х-3) = (10х+3)(х+1)

10х² + 2х - 15х -3 = 10х² + 3х + 10х + 3

10х² - 10х² + 2х - 3х - 15х - 10х = 3 + 3

-26х = 6

х = 6/(-26)

х = -6/26 = -3/13

Похожие вопросы
Предмет: Алгебра, автор: zeroedcsdh